PENGARUH KOMPOS TANDAN KOSONG KELAPA SAWIT DAN ABU BOILER DI LAHAN GAMBUT TERHADAP PERTUMBUHAN DAN PRODUKSI SEMANGKA (Citrullus lanatus) - Veranika Veranika; Nelvia Nelvia; Al Ikhsan Amri (DINAMIKA PERTANIAN, 2018)
The research aims to obtain a combination of doses of palm oil empty bunches compost (POEBC) and boiler ash to increase the growth and yield of watermelons on peatlands. The experiment was conducted in factorial form using Completely Randomized Design (CRD). The first factor was POEBC consisting of 4 levels (0; 7,5; 10 and 12,5 ton/ha) and the second factor is boiler ash consisting of 4 levels (0; 2,5; 5 and 7,5 ton/ha), and each combination was repeated 3 times. Parameters observed were plant length, stem diameter, flowering age, the weight of fruit per plant, and yield per plot (15 m2). The results showed that the combination of POEBC dosage 12,5 ton/ha and boiler ash dosage 7,5 ton/ha increased the plant length, stem diameter, the weight of fruit per plant 453%, yield per plot 139% and flowering 8 days faster compared to control (without treatment).